2015
DOI: 10.2737/nrs-rb-95
|View full text |Cite
|
Sign up to set email alerts
|

Forests of Vermont and New Hampshire 2012

Abstract: The first full remeasurement of the annual inventory of the forests of Vermont and New Hampshire was completed in 2012 and covers nearly 9.5 million acres of forest land, with an average volume of nearly 2,300 cubic feet per acre. The data in this report are based on visits to 1,100 plots located across Vermont and 1,091 plots located across New Hampshire. Forest land is dominated by the maple/beech/birch forest-type group, which occupies 60 percent of total forest land area. Of the forest land, 64 percent con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…This report systematically developed some well‐ordered strategies and summarized the conservation activities of local organizations and agencies since the 1990s, leading to 21% of the watershed (about 56,100 acres) permanently protected by 2004. Morin et al () pointed out that approximately 15,000 acres of net forest were gained as a result of reforestation and succession in former agricultural areas from 2007 to 2012. Hence, corresponding evidence of opposite vegetation cover change could be detected in these regional‐scale studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report systematically developed some well‐ordered strategies and summarized the conservation activities of local organizations and agencies since the 1990s, leading to 21% of the watershed (about 56,100 acres) permanently protected by 2004. Morin et al () pointed out that approximately 15,000 acres of net forest were gained as a result of reforestation and succession in former agricultural areas from 2007 to 2012. Hence, corresponding evidence of opposite vegetation cover change could be detected in these regional‐scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although some regions are experiencing modest population growth, low‐density residential and commercial development still has been trending upward in recent decades, which leads to a large land transformation and increased water consumption (Clay, Deininger, Hafner, & Nedeau, ). Forest land area is projected to decline by 3.2%–5.8% and 8.4%–11.5% in Vermont and New Hampshire from 2010 to 2060, respectively (Morin et al, ). Decreasing vegetation cover caused by population growth and urbanization can have a large influence on run‐off as hydrological processes are altered by evapotranspiration, interception, and infiltration (Archer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the nearby states of Vermont and New Hampshire, Morin et al (2015) reported the presence of invasive plants in 24.5 percent of Vermont plots and 11.2 percent of New Hampshire plots. The relatively high number of IPS across New York is a concern as these invaders can cause detrimental forest changes.…”
Section: What This Meansmentioning
confidence: 99%
“…In addition to programmatic factors, small property sizes prevent small forest landowners from participating in California’s emerging carbon market, particularly in the Northeast, where family forest owners live on an average of just 50.66 acres of forest[ 8 ]. With approximately 61% of forest land in Vermont in the hands of family forest owners, low participation removes large quantities of valuable forest carbon from offset markets[ 19 ]. Therefore, it is important to better understand small landowners’ preferences for forest carbon credit protocol design in order to encourage their participation in the carbon offset market.…”
Section: Introductionmentioning
confidence: 99%